Using qualitative methodology in ergonomics: theoretical background and practical examples - Hignett, Sue (2001)
Qualitative methodology offers the opportunity for ergonomists to investigate work problems and research questions using context-sensitive tools for data collection and analysis. This is particularly useful in contexts with complex social and cultural dimensions, for example the high level of emotional and intimate personal interactions between staff and patients in the health care industry.